(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Public Archaeology as a concept is generally defined as civic involvemen during the various public phases of Cultural Resources Management. The practice of archaeology in South Africa seldom extends towards public participation in archaeological activities or the production of knowledge. Public Archaeology constitute the active participation of the public in the archaeological excavation and the documentation of an archaeological site. The aim of the East Fort Archaeological Project is to provide an opportunity to members of the public interested in archaeology, as well as to assist high school learners and prospective tertiary students considering archaeology as a career, to participate in an active archaeological project regardless of their skills level. Initially the project was only aimed at high school learners, since heritage is included in the History curriculum for high school learners. Later members of the general public and primary school learners were included due to the interest shown in the project. This article provides an overview of the project from 2013 to the present. It looks at the different aspects thereof, consisting of an orientation course, educational excursion and practical archaeological field work. The project can be considered a success as it proves that the public can participate in and assist with the production of archaeological knowledge. It is foreseen that History teachers could be involved in similar projects that can be used to make history come alive for learners. It is also a first step in creating a heritage-literate society.